2023
DOI: 10.3390/jof9050521
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes from the Fungus Antrodiella albocinnamomea with Cytotoxicity and Antibacterial Activity

Abstract: Eight new sesquiterpenes, namely, albocinnamins A−H (1−8), along with two known ones (9 and 10), have been isolated from the fungus Antrodiella albocinnamomea. Compound 1 possesses a new backbone that might be derived from cadinane-type sesquiterpene. Structures of the new compounds were elucidated by detailed spectroscopic data analysis, single-crystal X-ray diffraction, and ECD calculations. Compounds 1a and 1b showed cytotoxicity against SW480 and MCF-7 cells, with IC50 values ranging from 19.3 to 33.3 μM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Multiple studies have demonstrated that certain mushrooms exhibit remarkable functional effects, encompassing antioxidant, immunomodulatory, and anti-tumor activities. In particular, polysaccharides in mushrooms have attracted much attention because of their high efficiency, low toxicity, and wide availability [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that certain mushrooms exhibit remarkable functional effects, encompassing antioxidant, immunomodulatory, and anti-tumor activities. In particular, polysaccharides in mushrooms have attracted much attention because of their high efficiency, low toxicity, and wide availability [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%